Pengaruh Manajemen Pelayanan Terhadap Kinerja Pegawai Di Kantor Sekretariat Dewan Kabupaten Enrekang - Syah, Alfin Firman; Hakim, Lukman; Tahir, Nurbiah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study aims  to: determine  service  management at the Secretariat  Office  of the Enrekang  Regency  Council,  determine  the  performance  of  employees  at  the  Enrekang Regency Council Secretariat Office, and determine the effect of service management on employee performance at the Enrekang Regency Council Secretariat Office. Data collection using  a  questionnaire  that  was  distributed  to  50  employees.  The  data  analysis  used descriptive analysis and simple linear regression analysis. The results showed that: service management was in good category with performance appraisal as the most prominent aspect, employee performance was in good category with the most prominent aspect of responsibility and service management had a positive and significant effect on the performance of the employees of the Enrekang Regency Council Secretariat office. Thus, the higher the service management provided, the higher the employee's performance. Through performance, it is known the level of achievement of the results that have been achieved, or it will be known how far the implementation of tasks has been carried out. Keywords: Service Management, Employee Performance.